PENINGKATAN HASIL BELAJAR SIFAT-SIFAT BANGUN RUANG DENGAN METODE INKUIRI DI KELAS IV SD - Kartina, Kartina (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2013)
This study begins with low learning outcomes geometrical properties in the class IV SDN 13 Gunung Tuleh. This is because teachers are still predominantly use lecture method. And to deliver material geometrical properties needed for effective learning method and fun, so that students can understand the geometrical properties and not feel bored. Implementation of learning through Inkury method is by these steps: 1) the orientation phase, 2) the stage of formulating the problem, 3) the stage of formulating hypotheses, 4) stage of collecting data, 5) stage of formulating conclusions. Research purposes to describe the planning, implementation and learning outcomes attributes geometrical properties with the inquiry method in SDN 13 Class IV Gunung Tuleh Muara Kiawai district Pasaman Barat. This research is action research (class action research), this study used qualitative and quantitative approaches. This study includes (1) Planning, (2) implementation, (3) observation, (4) Refeleksi. This study was conducted in two cycles. The subjects were teachers and fourth grade students of SDN 13 Gunung Tuleh. The results showed that the method of inquiry to improve student learning outcomes. The results of the first cycle of the meeting I pointed assessment of the implementation plan learning percentage of 50% with less criteria, implementation of aspects of the teacher shows the percentage of 57% with less criteria, and implementation aspects of the percentage of students demonstrating less than 54% of the criteria. I Cycle II implementation plan meeting the learning criterion percentage of 68% with enough teachers with the implementation of aspects percentage of 71% with both criteria, and implementation aspects percentage of students with 71% of the criteria well. Cycle II implementation plan with a percentage of 85% learning criterion very well, the percentage of teachers with the implementation of aspects of the 92% criterion is very good, and the implementation of aspects of the percentage of students with an excellent 89% criteria. It can be concluded study geometrical properties using the inquiry method of learning outcomes increases. Kata kunci: peningkatan; hasil; belajar; metode; inkuiri;